Determinants of career choices og high school graduates from three groups in Mindanao - Amilbahar, Carmat 1942-
The Rainard Brainard Occupational Preference Inventory was used to measure the vocational interests of 503 Tausug, Samal, and Maguindanao college freshmen enrolled in 8 public and private colleges and universities in Cotabato and Sulu. Correlation coefficient, Pearson's r, chi-square, multiple regression analysis and ANOVA were used. The career choices vary with age, sex, father's education and occupation, mother's education and occupation, parent's income and ethnic grouping, and are related to high school subjects and mental ability. Maguindanaons chose education and social welfare; the Tausugs, commerce and engineering and the Samals, engineering and military careers.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Vocational guidance for minorities -- Philippines -- Mindanao; High school graduates -- Employment -- Philippines -- Mindanao